COMPARISON OF PLASMA VISCOSITY AND FIBRINOGEN CONCENTRATION IN HYPERTENSIVE AND NORMOTENSIVE DIABETICS - Khan, Taj Muhammad; Marwat, Mumtaz Ali; Rehman, Habibur (Journal of Ayub Medical College Abbottabad, 2005)
Background: Body weight, body mass index, fibrinogen concentration and relative plasma viscosity can contribute to the development of hypertension in diabetics. This study compares body weight, body mass index, fibrinogen concentration and relative plasma viscosity between hypertensive diabetics, normotensive diabetics and healthy controls. Methods: The present study was carried out on normotensive and hypertensive diabetics taken from medical OPD of Saidu group of teaching hospitals, Swat. A group of healthy male subjects between 30-60 years of age from the staff members of Saidu Medical College, Swat was also included. Each group comprised of 35 subjects. Systolic and diastolic blood pressures, body weight, height, body mass index, fibrinogen concentration and relative plasma viscosity were measured and compared. Results: Body weight, body mass index, fibrinogen concentration and relative plasma viscosity were all significantly more in hypertensive diabetics than normotensive diabetics and healthy control subjects. Conclusion: The onset of the complications is different in the two groups of diabetics (hypertensive and normotensive), earlier in hypertensive diabetics and delayed in normotensive diabetics. Keywords: Plasma viscosity, Fibrinogen, Diabetes, Hypertension